Routledge handbook of Latin American security - Mares, David R.; Kacowicz, Arie Marcelo (London : Routledge, Taylor & Francis Group, 2016)
'This new Handbook is a comprehensive collection of cutting-edge essays on all aspects of Latin American Security by a mix of established and emerging scholars. The Routledge Handbook of Latin American Security identifies the key contemporary topics of research and debate, taking into account that the study of Latin America's comparative and international politics has undergone dramatic changes since the end of the Cold War, the return of democracy and the re-legitimization and re-armament of the military against the background of low-level uses of force short of war. Latin America's security issues have become an important topic in international relations and Latin American studies. This Handbook sets a rigorous agenda for future research and is organised into six key parts: - The Evolution of Security in Latin America - Theoretical Approaches to Security in Latin America - Different'Securities' - Contemporary Regional Security Challenges - Latin America and Contemporary International Security Challenges With a focus on contemporary challenges and the failures of regional institutions to eliminate the threat of the use of force among Latin Americans, this Handbook will be of great interest to students of Latin American politics, security studies, war and conflict studies and International Relations in general'--
Includes bibliographical references and index.
Keywords: Security, International -- Latin America; National security -- Latin America; Human security -- Latin America; Democracy -- Latin America; Latin America -- Politics and government